Macroeconomic Determinants of Islamic Stock Market Performance: An Analysis of Interest Rates, Inflation, Exchange Rates and Gold Prices - Layaman, Layaman; Abdul Wadud, Abdul Muizz; Jaelani, Aan; Mawaddah, Zazilatul (Li Falah: Journal of Islamic Economics and Business, 2024)
This study investigates how key macroeconomic variables influence the Islamic stock market in Indonesia through analysis of the Jakarta Islamic Index (JII). The research examines the impact of interest rates, inflation, exchange rates, and global gold prices on Islamic stock price movements, using monthly time series data from 2017 to 2021. The study employs multiple linear regression analysis with classical assumption tests to analyze the relationships between these variables. The findings reveal that interest rates have a significant positive effect on Islamic stock prices, while exchange rates demonstrate a significant negative impact. Inflation shows a negative but insignificant influence, and global gold prices exhibit a negative but statistically insignificant effect on the Islamic stock index. The model explains 69.8% of the variance in Islamic stock prices, indicating the substantial role of macroeconomic factors in determining Islamic stock market performance. These results provide valuable insights for investors, policymakers, and market participants in understanding the dynamics of Islamic stock markets and their relationship with broader economic conditions. The study contributes to the growing literature on Islamic finance by demonstrating how Sharia-compliant investments respond to various macroeconomic factors, offering practical implications for investment strategies and market regulation.